2022
DOI: 10.3390/biom12111657
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS Isomeric Profiling of N-Glycans Derived from Low-Abundant Serum Glycoproteins in Mild Cognitive Impairment Patients

Abstract: Mild cognitive impairment (MCI) is an early stage of memory loss that affects cognitive abilities, such as language or virtual/spatial comprehension. This cognitive decline is mostly observed with the aging of individuals. Recently, MCI has been considered as a prodromal phase of Alzheimer’s disease (AD), with a 10–15% conversion rate. However, the existing diagnostic methods fail to provide precise and well-timed diagnoses, and the pathophysiology of MCI is not fully understood. Alterations of serum N-glycan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…In addition to the N -glycan profiles of the S1 protein variants, we briefly investigated the differences in the isomeric expression across variants. The N -glycan isomeric separation was achieved using our previously developed methodology [ 38 ]. Supplementary Table S3 shows the relative abundance of the identified isomeric N -glycans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the N -glycan profiles of the S1 protein variants, we briefly investigated the differences in the isomeric expression across variants. The N -glycan isomeric separation was achieved using our previously developed methodology [ 38 ]. Supplementary Table S3 shows the relative abundance of the identified isomeric N -glycans.…”
Section: Discussionmentioning
confidence: 99%
“…A previously developed in-house methodology [ 38 ] was used to complete the N -glycan profile of the SARS-CoV-2 spike protein S1 of the variants alpha, beta, gamma, delta, epsilon, eta, iota, kappa, lambda, mu, and omicron. Two micrograms of the permethylated N -glycan sample were introduced into the LC-MS system.…”
Section: Methodsmentioning
confidence: 99%
“…The role of sialylated glycans was discussed by the Bhide group with regard to cancer. They observed that cancer cell lines exhibited an altered glycosylation pattern, which could aid cancer cell survival, drug resistance, and metastasis [61][62][63]. However, there is currently no research available on the presence of particular glycans and glycopeptides for NT1.…”
Section: Discussionmentioning
confidence: 99%
“…Omics is an emerging field that holds promise to shine light on the molecular mechanisms causing diseases [ 10 ]. Most recently, proteomics, glycomics, glycoproteomics, and metabolomics changes have been implicated in several diseases [ 11 , 12 , 13 , 14 , 15 , 16 ]. To facilitate better understanding of diseases, many omics fields have advanced methods for better identification of glycans, glycopeptides, and their isomers [ 17 , 18 , 19 , 20 ], and have developed several bioinformatic tools [ 21 ] that improve interpretations of omics data.…”
Section: Introductionmentioning
confidence: 99%